Transcriptome profiling of genes regulated by phosphate-solubilizing bacteria Bacillus megaterium P68 in potato (Solanum tuberosum L.) - Lin, Lizhen; Li, Chengchen; Ren, Zongling; Qin, Yuzhi; Wang, Ruilong; Wang, Jia; Cai, Jianying; Zhao, Lanfeng; Li, Xiaobo; Cai, Yanfei; Xiong, Xingyao (Frontiers in Microbiology, 2023)
In the present study, PSB were isolated from rhizosphere soil in soybean, the data of potato yield and quality revealed that the strain P68 was the most effective to promoting potato growth. The P68 strain (P68) is the Bacillus megaterium by sequencing and identification, with a P-solubilizing ability of 461.86 mg•L-1 . Compared with the control group (CK), P68 significantly increased the yield of potato commercial tubers by 17.02% and P accumulation by 47.88% in the field. Similarly, the pot trials showed that the application of P68 strain significantly increased the biomass, total phosphorus content of the potato plants and available phosphorus of the soil up by 32.33%, 37.50% and 29.15%, respectively. Compared with the CK, there were a total of 784 differential genes (DEGs) regulated when treated with P68, which 439 genes were up-regulated and 345 genes were down-regulated. Interestingly, most of the DEGs were mainly related to cellular carbohydrate metabolic process, photosynthesis and cellular carbohydrate biosynthesis process. A total of 46 taxonomic metabolic pathways in the Kyoto Encyclopedia of Genes and Genomes (KEGG) database were annotated to 101 DEGs found in potato roots, according to the KEGG pathway analysis. Compared with CK, most of the DEGs were mainly enriched in glyoxylate and dicarboxylate metabolism (sot00630), nitrogen metabolism (sot00910), tryptophan metabolism (sot00380) and plant hormone signal transduction (sot04075), and these DEGs might be involved in the interactions between Bacillus megaterium P68 and potato growth. The qRT-PCR analysis of differentially expressed genes showed that inoculated treatments P68 significantly up-regulated expression in the phosphate transport, nitrate transport, glutamine synthesis, and abscisic acid regulatory pathways, respectively, and the data from qRT-PCR were consistent with those obtained from RNA-seq. In summary, PSB may be involved in the regulation of nitrogen and phosphorus nutrition, glutaminase synthesis and abscisic acid-related metabolic pathways, this paper would provide a new perspective to study the molecular mechanism of potato growth promotion by PSB in the level of gene expression and related metabolic pathways in potato roots under the application of Bacillus megaterium P68.